PROGRAMA DE CONTROLE DE ENERGIAS PERIGOSAS: ESTUDO DE CASO EM ATIVIDADE DE MANUTENÇÃO NUMA REFINARIA DE PETRÓLEO - Rinaldi, Fernando da Silveira Bulcão (2008)
This study aims to present a proposal for implementation of a planning tool in the management of maintenance, allowing the execution of work in a safe, minimizing the risks of proceeding, in terms of SMS, making safe and appropriate to release equipment for maintenance As well as the implementation of the work in processing plants and oil derivatives, thus providing the integration of the function to maintain the company's strategic objectives, as well as the preservation of assets and image of the corporation, which allows the continuation of operational and security sustainability of the business. In this sense, as an option methodology, structure is a case study focusing on the control of hazardous energy in activities to maintain a data-processing unit at an oil refinery. As a result it presents a proposal based on a robust planning and implemented, based on the model of the PDCA cycle, which involves people, procedures and management of the production process.